Peningkatan Aktivitas Belajar Peserta Didik Kelas VIIC SMPN 3 Sungai Kakap Melalui Model Think Pair Share Berbantuan PowerPoint - Titin Titin; Eko Sri Wahyuni; Erni Sulistiyowati (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study is motivated by the low activeness of students in class VII C SMP Negeri 3 Sungai Kakap during the science learning process so that it has an impact on student learning outcomes. This study aims to improve the learning activities of VII C grade students at SMP Negeri 3 Sungai Kakap on the topic of Indonesian ecology and biodiversity through the application of the Think Pair Share (TPS) model assisted by powerpoint. The type of research used is classroom action research in the form of two cycles and each cycle consists of two meetings. The research procedure went through four stages starting with planning, action implementation, observation, and reflection. A total of 32 students of class VII C in the 2023/2024 school year became the research subjects. Data collection was carried out using observation and documentation methods and the instrument used was the student learning activity observation sheet. The results showed that the percentage of students' learning activities in cycle I was 68.75% and in cycle II it was 88.44%. Based on these data, it is concluded that the application of the TPS model assisted by powerpoint can increase the learning activity of students in class VII C SMPN 3 Sungai Kakap, especially in the topic of Indonesian ecology and biodiversity.